Characterization of Four Copper Materials for Application as Reference Materials for High Precision Copper Isotope Analysis by Laser Ablation Inductively Coupled Plasma Multi-Collector Mass Spectrometry - Yang, Zhaoping; Jackson, Simon Edward; Skulski, Thomas (Frontiers in Chemistry, 2021)
Laser ablation inductively coupled plasma multi-collector mass spectrometry (LA-MC-ICP-MS) allows rapid, in situ, highly precise measurements of Cu isotope ratios of native Cu and Cu-bearing minerals. However, the National Institute of Standards and Technology Cu-metal isotope standard NIST SRM976 that is commonly used to calibrate LA-MC-ICP-MS Cu isotope measurements of native Cu is no longer available. We have investigated the suitability of four Cu metal materials, SSC-1, SSC-3 and SSC-4 (cathode Cu metal rods) and CUPD-1 (Cu anode sawings), originally developed by the Canada Centre for Mineral and Energy Technology (CANMET) as certified reference materials for trace element analysis, as Cu isotope reference materials for LA-MC-ICP-MS analysis and solution nebulization (SN) of Cu. The Cu isotopic composition and homogeneity of these four materials were characterised by SN- and LA-MC-ICP-MS, and are reported for the first time. The bulk Cu isotopic compositions, expressed as δ65CuSRM976 in per mil (‰) relative to NIST SRM976 with combined uncertainties (U, k = 2), of SSC-1, SSC-3 and SSC-4, determined utilizing SN-MC-ICP-MS, are identical within analytical uncertainty at 0.03 ± 0.07‰ (n = 29), 0.04 ± 0.04‰ (n = 28), and 0.05 ± 0.08‰ (n = 29), respectively; the composition of CUPD-1 is 2.14 ± 0.08‰ (n = 28). The compositions are 0.01 ± 0.07‰ (n = 29), 0.04 ± 0.06‰ (n = 29), 0.03 ± 0.06‰ (n = 28) and 2.15 ± 0.06‰ (n = 28), respectively, relative to the European Reference Material ERM®-AE633 Cu isotope standard. The Cu isotope homogeneity of the four new reference materials was assessed by determining whether multiple individual in situ Cu isotope measurements made by LA-MC-ICP-MS analysis (43 µm spot size), using each of the other three reference materials as a calibrator, approximate a single normal distribution. We also investigate whether there are statistically significant differences between the mean δ65Cu values of three independent data sets for each of the Cu isotope reference materials using one-way analysis of variance (ANOVA). Normality tests (graphical assessment of normal distribution quantile-quantile plots, and the Shapiro-Wilk, Jarque-Bera and reduced chi-squared statistic tests) show that: 1) the Cu isotope data acquired on SSC-1, SSC-3, SSC-4 and CUPD-1 do not depart significantly from a normal distribution, 2) the scatter of the Cu isotope data is due to analytical uncertainty with 95% confidence, and 3) there are no other significant sources of scatter; e.g. heterogeneity of the reference materials. The results of one-way ANOVA reveal that the mean difference of the δ65Cu value for each of the reference materials SSC-1, SSC-3, SSC-4 and CUPD-1 is statistically not significant at the 0.05 level. The mean δ65CuSRM976 values with combined uncertainties (U, k = 2) of SSC-1, SSC-3, SSC-4 and CUPD-1, determined by LA-MC-ICP-MS using each of the other three reference materials as a calibration standard, are 0.03 ± 0.09‰ (n = 132), 0.05 ± 0.09‰ (n = 154), 0.03 ± 0.09‰ (n = 144) and 2.14 ± 0.10‰ (n = 106), respectively. These values are in agreement with those determined by SN-MC-ICP-MS analysis at the 95% confidence level and have excellent precision (2 s.d. ≤ 0.10‰). These results suggest that SSC-1, SSC-3, SSC-4 and CUPD-1 can be considered isotopically homogeneous at a spatial resolution of 43 μm, and they are suitable reference materials for calibration and quality control of in situ and solution nebulization Cu isotope analyses of Cu.